Pengaruh Fraksi Massa Laminat Serat Bambu dan Bagasse terhadap Kekuatan Tarik dan Bending Material Komposit Sandwich Berbasis Asam Poli-Laktat - Aulia Kusumaningtyas (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Industrial progress and development have led to an increase in the use of environmentally unfriendly materials, such as plastics and synthetic resins in everyday life, resulting in water and soil pollution. A potential alternative to address these issues is the development of natural fiber-based composite materials. Therefore, this study aims to fill the gap by analyzing the effect of the mass fraction of bamboo and bagasse laminates on the tensile strength and bending strength of poly-lactic acid-based sandwich composites. The composite material manufacturing process was carried out using the hand lay-up method or manual manufacturing by layering the fibers and matrix. The tests carried out were tensile strength tests, bending strength tests, Fourier Transform Infrared Spectroscopy (FTIR) analysis which were then statistically analyzed using one-way ANOVA. The results of the study showed that variations in mass fractions affected the mechanical properties of sandwich composite materials. The results of the ANOVA analysis showed that variations in mass fractions significantly affected the tensile strength and elastic modulus values, but not significantly on the bending strength and bending modulus values.
Approved by Teddy
Keywords: Material Komposi; Asam Poli-Laktat; Kekuatan Tarik